Intramedullary Screws versus Kirschner Wires for Metacarpal Fixation, Functional, and Patient-Related Outcomes - Couceiro, Jose; Ayala, Higinio; Sanchez, Manuel; De la Red, Maria de Los Angeles; Velez, Olga; Del Canto, Fernando (The Surgery Journal, 2018)
Purpose The purpose of our study is to compare the intramedullary fixation of metacarpal fractures with cannulated headless screws and antegrade Kirschner wires in terms of final total active motion, grip strength, patient-related outcomes, need for casting, and return to work times.Methods The authors performed a retrospective review of the hospital records. Thirty fractures were included in the study, 19 in the screw fixation group, and 11 in the Kirschner wire group. Grip strength, and total active motion, was measured at the latest follow-up for both the injured and contralateral hand. Pain was measured on the visual analog scale. Patients were requested to fill a Quick disabilities of the arm and hand score (DASH) questionnaire at the latest follow-up. Satisfaction was measured on a scale from 0 to 10. The time to return to work was quantified from the accident to the point when the patient was back to active duty. Postoperative casting time was also quantified.Results The authors did not find any differences between the two groups in total active motion, grip strength, pain, satisfaction, or Quick DASH scores. We did find a difference in the return to work and casting times; these appeared to be shorter in the screw group.Conclusion Due to the small number of cases, we have been unable to clearly conclude that there were any benefits in the application of one particular technique when compared with the other.
Keywords: metacarpal; fracture; screws; wires; function